Model Pengembangan Bisnis Terintegrasi Pesantren Dengan Pendekatan Pemasaran Berbasis Syariah - Muhammad Tahir; Andi Dirga Nugraha; Siradjuddin Siradjuddin (Universitas Muhammadiyah Sumatera Utara, 2022)
Pesantren institutions have now become prima donna for parents. This is the impact of the bad image of public schools in various media. The old pesantren continued the process, and new, more innovative pesantren continued to emerge. The education system and pesantren institutions are developing rapidly, supported by facilities, infrastructure, and curriculum. They are always adaptive to the needs of the times. However, financial capital remains the main obstacle to the development of pesantren and the hopes of parents. The issue of halal centers is growing internationally. This makes the pesantren continue to offer applicable ideas to achieve financial independence. Then these institutions can become promising sharia tourism centers. An observant sharia marketing plan is the key. This article uses a qualitative literature study to collect data related to the theme of the article. It can be concluded that Islamic boarding schools have the potential to develop sharia tourism and integrated halal tourism to achieve financial independence. The concept of SET and sharia-based marketing are the 2 main things that significantly support this.Keywords: Business, Islamic Boarding School, Sharia Marketing, SET, Sharia Tourism.